2021
DOI: 10.1097/sap.0000000000002826
|View full text |Cite
|
Sign up to set email alerts
|

Routine Postoperative Antibiotics After Tissue Expander Placement Postmastectomy Does Not Improve Outcome

Abstract: Purpose In an attempt to reduce the incidence of infectious complications after tissue expander–based breast reconstruction, the routine administration of postoperative antibiotics regimen is common in many practices. In recent years, there has been a plethora of reports scrutinizing the prophylactic use of postoperative antibiotics in this setting. The aim of this study was to determine the efficacy of prolonged administration of postoperative antibiotics compared with perioperative-only antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…The types of procedures in the McCullough et al ( 14 ) and Ranganathan et al ( 15 ) studies were all immediate breast reconstruction approaches. In addition to this, subjects in three studies involved expander placement, which was performed in both the anterior thoracic and submuscular planes ( 14 , 16 , 20 ). Moreover, five studies addressed the duration of antibiotic application after breast implant reconstruction, including >48 h and until drainage removal ( 16 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The types of procedures in the McCullough et al ( 14 ) and Ranganathan et al ( 15 ) studies were all immediate breast reconstruction approaches. In addition to this, subjects in three studies involved expander placement, which was performed in both the anterior thoracic and submuscular planes ( 14 , 16 , 20 ). Moreover, five studies addressed the duration of antibiotic application after breast implant reconstruction, including >48 h and until drainage removal ( 16 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, subjects in three studies involved expander placement, which was performed in both the anterior thoracic and submuscular planes ( 14 , 16 , 20 ). Moreover, five studies addressed the duration of antibiotic application after breast implant reconstruction, including >48 h and until drainage removal ( 16 20 ). For the specific application of antibiotics, four of the included studies noted the use of cephalosporin antibiotics for general patients and clindamycin or vancomycin for allergic patients ( 14 , 17 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Im Gegensatz dazu ließ sich ein entsprechender Vorteil durch eine Verlängerung der intravenösen Antibiose gegenüber einer Antibiose für 24 Stunden nicht zeigen (RR = 0,80, 95%-KI: 0,60 – 1,08, p = 0,13). Daher wird eine perioperative Antibiose lediglich für maximal 24 Stunden empfohlen (LoE 2a/B/+) 17 , 18 .…”
Section: Brustrekonstruktionunclassified
“…11 Conversely, numerous studies demonstrated no effect of postdischarge antibiotics on SSI following mastectomy, although many of these studies lacked sufficient power to detect an association with only a moderate effect. [12][13][14][15][16][17][18][19][20][21] Exposure of patients to prolonged antibiotic regimens results in higher costs, selection of antibiotic-resistant organisms, and increased risk of Clostridioides difficile infection. [22][23][24][25][26] The importance of outpatient antibiotic stewardship is increasingly recognized because outpatient antibiotic prescriptions constitute the majority of antibiotic use.…”
mentioning
confidence: 99%